# Solve the followi

i) By elimination method

x + y = 5.............(i)

2x - 3y = 4..........(ii)

Multiplying equation (i) by 2 we get,

2x + 2y = 10 ..............(iii)

Subtracting equation (ii) from equation (iii) we get,

5y = 6

y =

Putting value of y in equation (i). we get,

x =

By substitution method

x + y = 5 ...........(i)

2x - 3y = 4 ......................(ii)

from equation (i)

x = 5 - y................(iii)

Putting value of x from equation (iii) to equation (ii) we get,

2(5 - y) - 3y = 4

= 10 - 2y - 3y = 4

= -5y = -6

= y =

Putting value of y in equation (iii) we get,

x = .

ii) By elimination method

3x + 4y = 10 ..............(i)

2x - 2y = 2.................(ii)

Multiplying equation (ii) by 2 we get,

4x - 4y = 4 ...............(iii)

Adding equations (i) and (iii) we get,

7x = 14

= x =

Putting value of x in equation (i) we get,

3 (2) + 4y = 10

4y = 10 - 6 = 4

y =

By substitution method

3x + 4y = 10 ..............(i)

2x - 2y = 2.................(ii)

From equation (ii)

2x = 2 + 2y
Dividing both side by 2, we get
x = 1 + y

putting value of x in equation (i) we get,

3(1 + y) + 4y = 10
3 + 3y + 4y = 10
7y = 7
y = 1

and
x = 1 + y = 1 + 1 = 2

(iii) By elimination method

3x - 5y = 4................(i)

9x - 2y = 7..........(ii)

Multiplying equation (i) by 3 we get,

9x - 15y = 12.................(iii)

Subtracting equation (ii) from (iii) we get,

- 13y = 5

= y =

Putting value of y in equation (i) we get,

3x -

3x +

Taking LCM,

By substitution method

3x - 5y = 4................(i)

9x - 2y = 7..........(ii)

From equation (i)

x =

Putting value of x in equation (ii) we get,

=

=

= 13y = -5

y =

Putting value of y in equation (i) we get

3x -

3x = 4 -

= x =

iv) By elimination method

.....(i)

=

Multiplying equation (i) by 2, we get,

x +

Subtracting equation (ii) from equation (iii) we get,

=

= y =

Putting value of y in equation (ii) we get,

x +

= x - 4 = - 2

= x = 2

By substitution method

.....(i)

=

From equation (ii) we get,

x = 3 +      (iii)

Putting value of x in equation (i) we get,

=

=

= 5y = - 6 - 9 = - 15

= y =

Putting this value in (iii), we get
x = 3 - 1 = 2

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Merchant of Venice (Summary and Important Questions)30 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Solve each of theRS Aggarwal - Mathematics

If 2x – 3y = 7 anRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics